The Dynamics Of Australian Stock Indices And Commodities Based On Mgarch-dcc And Wavelet Techniques - Ahmad Monir Abdullah; Mohd Fahmi Ghazali; Mohd Hasimi Yaacob; Abul Mansur Mohammed Masih; Hishamuddin Abdul Wahab (Taylor and Francis Group, 2024)
Indexed by WOS/SCOPUS/ERA